781hw11sol

# 781hw11sol - 18.781, Fall 2007 Problem Set 11 Solutions to...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 18.781, Fall 2007 Problem Set 11 Solutions to Selected Problems Problem 1 (a) It is very easy to find the sequence which satisfies given condition. For example, a n := 1 n (Note that this sequence has no zero term.) Then P N = Q N n =1 a n = 1 n ! , and the limit of P n is clearly 0. (b) Write as following ; Y n =1 a n = Y n =1 (1 + ( a n- 1)) . Let b n := a n- 1, then to show lim n b n = 0 is equivalent to show that lim n a n = 1. For the convergent infinite product, by our definition, lim n P n = where 6 = 0. Then lim n a n = lim n P n P n- 1 = lim n P n lim n P n- 1 = = 1 , as desired. (c) Think of b n = 1 n . Then 1 + b n = n +1 n , and we have P N = N Y n =1 n + 1 n = 2 1 3 2 N + 1 N = N + 1 . As N , P N , so it does not converge. (d) When a n > 0 for all n , we can say that log( P N ) = N n =1 log a n . Hence, [ P n converges nonzero number] is equivalent to [ n =1 log a n converges]. Therefore it is enough to show that X p log([1- p- s ]- 1 ) = X p log p s p s- 1 = X p log 1 + 1 p s- 1 < . To show that, I claim that If x > 0, then log(1 + x ) x . 1 It is not hard to prove this. For example, let f ( x ) = x- log(1 + x ). Then f (0) = 0 and f ( x ) = 1- 1 1+ x =- x 1+ x < 0, hence f is decreasing in [0 , ], so 0 = f (0) f ( x ), and we get the conclusion....
View Full Document

## This note was uploaded on 04/28/2009 for the course MATH 18.781 taught by Professor Brubaker during the Spring '09 term at MIT.

### Page1 / 4

781hw11sol - 18.781, Fall 2007 Problem Set 11 Solutions to...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online